Biodegradation of chromium by laccase action of Ganoderma multipileum - Maha A. Alshiekheid; Aisha Umar; Fuad Ameen; Sami A. Alyahya; Laurent Dufossé (Journal of King Saud University: Science, 2023)
Laccase is a fungal enzyme that play a crucial role in bioremediation. The purified laccase from Ganoderma multipileum and its effectiveness in bioremediation of Cr (VI) was determined in this study. Two strains of G. multipileum were identified by ITS sequences and their phylogeny was compared with G. multipileum taken from GenBank (KF494997, LC149613, MG739453, MG739455). The fungi were grown on guaiacol substrate for laccase optimization using different environmental and nutritional conditions. Laccase Glacc113 (75 kDa) was partially purified and characterized under different parameters. Glacc113 (GIAPTAD) was confirmed by using a Precise Protein Sequencing System to analyze sequence of N-terminal amino acid. Laccase exhibited maximum optimal activity (1355.5 ± 8.8 U/L) at pH 3.0 and can tolerate the maximum temperature upto 70 °C. During submerged fermentation, on 7th day after inoculum of 3 fungal discs at 100 rpm yielded maximum laccase. The production of laccase increased by optimization of inorganic and organic nitrogen and carbon sources. The purified laccase from G. multipileum was used to reduce (>94%) 100 μg/mL of Cr (VI) into less toxic chromium Cr (III). The catalytic kinetic parameters Vmax and Km for guaiacol were 1.817 (mM min−1) and 1.4617 (mM), respectively. This study determined the conditions that enhance production and an ecofriendly approach to bio remediate the Cr (VI) to Cr (III). The purified enzyme exerted maximum durability and reliability for industrial usage also.